The right to life and the Jus ad Bellum: belligerent equality and the duty to prosecute acts of aggression - Jackson, M; Akande, D (Cambridge University Press, 2022)
General Comment 36 of the Human Rights Committee, adopted in 2018, asserts that ‘States parties engaged in acts of aggression as defined in international law, resulting in deprivation of life, violate ipso facto article 6 of the Covenant.’ One question about this claim is whether it reduces incentives for compliance with international humanitarian law for States and their agents—incentives provided through the principles of belligerent equality and combatant immunity. It is argued that it does not do so—such a worry about incentives is not a reason to reject the claim in General Comment 36. In the process, it can also be shown that, if accepted, this claim is interesting in another way: it entails, in effect, a duty on States to prosecute acts of aggression insofar as they entail killing, as they often will. This itself is doctrinally innovative. As to who is to be prosecuted, it is the political and military leadership of the State. It is their decision to wage war unlawfully that renders the killings arbitrary.